A novel diagnostic algorithm for heparin‐induced thrombocytopenia. (13th May 2018) - Zheng, G.; Streiff, M. B.; Allison, D.; Takemoto, C. M.; Salimian, K.; Morris, P.; Jani, J.; McCord, R.; Kickler, T. S.
Abstract: Introduction: While diagnostic algorithm using PF4‐heparin enzyme‐linked immunosorbent assay (ELISA) optical density (OD), and heparin neutralization assay (HNA), or 4T score have been proposed to replace serotonin‐release assay (SRA) for heparin‐induced thrombocytopenia (HIT), their performance against SRA is unclear. In this study, we proposed and validated the performance of a new algorithm combining PF4‐heparin ELISA optical density (OD), HNA and 4T score against SRA for HIT diagnosis. Methods: Heparin neutralization assays were performed on specimens submitted for HIT testing with positive PF4‐heparin ELISA from December 2015 to September 2017, which were separated into a "training" and a "validation" data set. 4T scores were calculated for ELISA positive cases. Results: A total of 123 consecutive unique patient samples had positive PF4‐heparin ELISA with also HNA data, SRA data, and 4T scores available. Compared to SRA, a "laboratory criteria" (ELISA OD ≥ 1.4 and HNA ≥ 70%) had a sensitivity of 88% (14/16) and specificity of 91% (42/46), and a "combined criteria" (4T score = 8, or 4T score = 6 or 7 and ELISA OD ≥ 1.0, or 4T score = 4 or 5 and ELISA OD ≥ 2.0) had a sensitivity of 75% (12/16) and specificity of 98% (45/46) in the training data set. Laboratory and combined criteria had 90% (56/62) concordance rate. Importantly, for these concordant cases, the diagnostic specificity is 100% (46/46). Based on the data, a novel diagnostic algorithm combining these 2 criteria was proposed and validated prospectively. Conclusion: A novel algorithm has high diagnostic accuracy and potentially could eliminate the need for SRA testing in at least 90% patients with suspected HIT.